Converting To Online Course And Program Delivery: The University Of South Australia Case Study - King, Bruce; McCausland, Holly; Nunan, Ted (International Review of Research in Open and Distributed Learning, 2001)
The University of South Australia's (UniSA) approach to converting its distance education programs to online delivery is to manage it as a part of establishing an online teaching and learning environment for all of its programs. UniSA's move to online teaching and learning derives from a clear vision of its future, is informed and directed by a comprehensive framework for teaching and learning, and enabled by appropriate structures, processes and resources. The institution has chosen to develop a relatively low-cost, easy to use online teaching and learning environment that has facilitated large-scale conversion to the online mode for all teaching and learning, including traditional distance education.